Chemical reactions in H2O:CO interstellar ice analogues promoted by energetic heavy-ion irradiation. Issue 2 (27th January 2022) - de Barros, A L F; Mejía, C; Seperuelo Duarte, E; Domaracka, A; Boduch, P; Rothard, H; da Silveira, E F
ABSTRACT: H2 O:CO, at concentrations of (3:2) and (10:1), was condensed on CsI substrate at 15 K and irradiated with 46-MeV 58 Ni 11 + ion beam. Radiolysis induced by fast heavy ions was analyzed by infrared spectroscopy (FTIR). The formation of nine molecular species: CO2, H2 O2, HCOOH, HCO, H2 CO, 13 CO2, CH3 OH, O3, and C3 O2 was observed. For both concentrations, carbon dioxide (CO2 ), formaldehyde (H2 CO), formic acid (HCOOH), and hydrogen peroxide (H2 O2 ) are the most abundant products species, and tricarbon dioxide (C3 O2 ) is much less abundant. Precursor destruction cross-sections and formation cross-sections of products are determined. The CO destruction cross-section for the (3:2) concentration is almost five times higher than that of water, while those for the (10:1) concentration are practically the same. Atomic sputtering yields are estimated for the two ice films, the total mass sputtered is approximately 2.5 × 10 6 u per impact. These results contribute to figure out the chemical pathways of compounds synthesized from the two most abundant organic species (H2 O and CO) observed in the ices of grain mantles of the circumstellar envelopes and interstellar medium. In additional, the finding results reveal that molecular astronomical percentages are comparable to those obtained after 15 eV molec −1 of deposited dose in current experiments compared with the relative concentration of molecules in solid phase observed in MYSO, LYSO, BG Stars, and Comets.